Pengaruh Penambahan Tepung Daging Ikan Patin (Pangasius hypophthalmus) Terhadap Tingkat Kesukaan Kulit Macaron - Rahayu, Wanda Sri; Junianto, Junianto; Nurhayati, Atikah; Rostini, Iis (Jurnal Perikanan Unram, 2025)
Striped catfish meat flour contains a valuable source of protein that can be utilized as an additive in the production of baked goods such as macaron shell. This study aims to determine the right amount of addition of striped catfish meat flour (Pangasius hypophthalmus) in making macaron shell so as to produce the most preferred product. This research was conducted from December 2024 to May 2025 at the Fishery Product Processing Technology Laboratory, Joint Building of Fisheries and Agriculture, Fishery Product Processing Laboratory, Building 2 FPIK Unpad, and Laboratory Services UPTD Testing and Application of Quality of Fishery Products Cirebon. The method used in this study is an experimental method, namely the manufacture of macaron shell which is given the addition of striped catfish meat flour with 4 different addition treatments (0%, 2.5%, 5% and 7.5%) with 25 semi trained panelists as replicates to determine the level of panelist preference for macaron shell.